Urgensi Pengembangan Regulasi Pengelolaan Ziswaf Lembaga Pendidikan Pesantren - Zuhirsyan, Muhammad; Supaino, Supaino; Suhendar, Asep Dadan; Taufik, Yuyun; Nurmansyah, Andry (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
The establishment of OJK is to organize an overall supervisory and regulatory system, especially in financial sector activities, both in non-bank and banking institutions. OJK has three objectives, namely creating a financial services sector that is contributive to equal distribution of wealth, creating a financial services sector that is stable, foreign-powered, and realizing financial services that are inclusive for society by providing credible protection to the consumers. This study aims to find out what regulations are issued by the Financial Services Authority institutions to protect the consumers who use peer to peer lending services and what sanctions are issued by the Financial Services Authority institutions if the perpetrators of financial services violate the provisions in the Financial Services Authority regulations. The method used in this research is descriptive method with a qualitative approach.In this case the Financial Services Authority issues regulations concerning the Consumer Protection in the Financial Services Sector. And if a financial service actor violates or does not comply with the regulations made by OJK, he will receive sanctions as stated in the regulation Number: 1/POJK.07/2013, if a financial service actor violates the provisions in OJK regulations, he will be subject to administrative sanctions, namely written regulations, Fines or paying a certain amount of money, Limitation of business activities, Freezing of business activities, as well as revocation of licenses for business activities. Keywords: Role, OJK, Protection, Consumers, Sharia Maqasid.